Rare case of human Streptococcus suis purpura fulminans at Prof. Ngoerah Hospital, Denpasar, Bali - Nara Dhany, Henri; Tarini, Ni Made Adi; Putrawan, Ida Bagus Putu; Pinatih, Komang Januartha Putra (Journal of Clinical Microbiology and Infectious Diseases, 2024)
Background: Streptococcus suis (S. suis) is a zoonotic bacterium capable of causing severe infections in humans, particularly those with occupational exposure to pigs or pork products. Notable manifestations include meningitis, endocarditis, sepsis, and distinct skin conditions such as purpura and necrotic lesions. Southeast Asia reports the highest incidence, correlating with prevalent pig farming practices. Though infrequent, S. suis infections can lead to severe outcomes if not promptly diagnosed and treated. Case Presentation: We present a case involving a 73-year-old Balinese man without recent exposure to pigs or pork but with a history of pork consumption six months prior. He was admitted with symptoms including skin discoloration, respiratory distress, and loss of consciousness. Physical and laboratory examinations revealed pleural effusion, pneumonia, and high procalcitonin levels. Blood cultures identified S. suis, confirmed by VITEK® 2 system with susceptibility to multiple antibiotics, except tetracycline. Despite initial treatment with ceftriaxone, azithromycin, and levofloxacin; the patient’s condition deteriorated, resulting in a fatal outcome. Conclusion: This case underscores the importance of early diagnosis and rapid antibiotic intervention in S. suis infection. Delay in hospitalization significantly impacts prognosis, and timely, targeted treatment could improve survival rates. Enhanced awareness and preventive strategies in high-risk areas are vital to reducing the incidence and mortality associated with this infection.